My "r" sound box - Moncure, Jane Belk; Thornburgh, Rebecca McKillip (Mankato, MN Child's World, 2019)
"Little r has an adventure with items beginning with his letter's sound, such as a rooster, a raccoon, and a rowboat and raft on a rainy river."--Publisher.
108228
Keywords: Alphabet -- Juvenile fiction; Alphabet books; Readers (primary).; Nonfiction; Fiction; Juvenile works